การศึกษาความสัมพันธ์ระหว่างขนาดของครัวเรือนและความอยู่ดีมีสุขระดับปัจเจกบุคคล: กรณีศึกษาผู้สูงอายุในเขตกรุงเทพมหานคร (AN EXPLORATORY STUDY OF THE RELATIONSHIP BETWEEN HOUSEHOLD SIZE AND INDIVIDUALS’ SUBJECTIVE WELL-BEING IN CASE OF ELDERLY’S LIVING IN BAN - ประไพพานิช ณัฐญา (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
This study aims to analyze the relationship between household size and individual subjective well-being in the case study of elderly in Bangkok who are 60 years old or older. Primary data were collected through questionnaires from 400 elderly persons. This study applied Generalized Order Logit and found that household size, the number of children, female, age, high income, good health and having a job were positively correlated with the subjective well-being of the elderly. The factors that have a negative relationship to the subjective well-being of the elderly were their feeling of having a lot of debt. Knowing the relationship of the factors, it can be used as an important information to prepare for the full integration into the aging society and to figure out the most suitable ways to improve elderly’s well-being. According to the results, this study suggests that the government attaches importance to the size of the household and to the child, and encourages families to have more children particularly for spouses who have just married or are not planning to have children. In addition, family members should stay home with the elderly, understand and give respect to them, and taking care them on the basis of love and gratitude.